Desain Kendali Pembangkit Listrik Tenaga Pikohidro Berbasis Ant Colony Optimization (ACO) - Muhamad Afif Dwi Wijaya; Machrus Ali; Rukslin Rukslin; Muhammad Agil Haikal (Universitas Darul Ulum, 2023)
Energy sources that are often used to generate electricity are non-renewable energy sources which, if used continuously, will run out, such as petroleum, natural gas and coal. So, renewable energy sources are needed which are in abundant supply and do not run out quickly, one of which is water energy. Picohydro power plants (PLTPH) are an alternative small-scale power plant that can be applied in rural areas where there is a river flow that has a continuous water discharge and a relatively low water fall to drive turbines that can produce electrical power. To be able to produce electrical power with such potential, a pico-hydro power plant is needed. To optimize the performance of a picohydro power plant, a controller called PID (Proportional Integral Derivative) is needed. Then this PID is combined with the ACO (Ant Colony Optimization) method. ACO is a method for optimizing PID control parameters in a system adapted from the ability of an ant colony to find the shortest path to a food source from its nest